Risk factors for human papilomavirus infection among women in Portugal: the CLEOPATRE Portugal Study - Pista, A (2012)
OBJECTIVE: Human papillomavirus (HPV) is responsible for a range of diseases, including cervical cancer. The primary objectives of the CLEOPATRE Portugal study were to estimate the overall and age-stratified prevalence of cervical HPV infection and to assess HPV prevalence and type-specific distribution by cytological results among women aged 18 to 64 years, who reside in mainland Portugal. MATERIALS AND METHODS: This cross-sectional population-based study recruited women aged 18 to 64 years, according to an age-stratified sampling strategy, who attended gynecology/obstetrics or sexually transmitted disease clinics across the 5 regional health administrations in mainland Portugal between 2008 and 2009. Liquid-based cytology samples were collected and analyzed centrally for HPV genotyping (clinical array HPV 2 assay) and cytology. Prevalence estimates were adjusted for age using 2007 Portuguese census data. RESULTS: A total of 2326 women were included in the study. The overall prevalence of HPV infection in the study was 19.4% (95% confidence interval, 17.8%-21.0%), with the highest prevalence in women aged 18 to 24 years. High-risk HPV types were detected in 76.5% of infections, of which 36.6% involved multiple types. The commonest high-risk type was HPV-16. At least 1 of the HPV types 6/11/16/18 was detected in 32.6% of infections. The HPV prevalence in normal cytology samples was 16.5%. There was a statistically significant association between high-risk infection and cytological abnormalities (P < 0.001). CONCLUSIONS: This is the first population-based study to quantify and describe cervical HPV infection in mainland Portugal. This study provides baseline data for future assessment of the impact of HPV vaccination programs.